House on the Gulf - Haddix, Margaret Peterson (New York Simon & Schuster Books for Young Readers, 2004)
A sixteen-year-old boy arranges a house sitting job for the summer, but he starts acting strangely after his family moves in, and his sister begins to suspect they are not supposed to be there.
730L
008-012.
A Junior Library Guild selection.
84810
Keywords: Mystery and detective stories; Housesitting -- Juvenile fiction; Grandparents -- Juvenile fiction; Florida -- Juvenile fiction